Formation and dissolution of conductive channels in an Ag2S-islands network. (26th May 2020) - Ojima, Keita; Hasegawa, Tsuyoshi; Naitoh, Yasuhisa; Shima, Hisashi; Akinaga, Hiroyuki
Abstract: A network that shows dynamical change in response to each input pattern works as a reservoir. In this study, we propose to use a network of Ag2 S islands for reservoir computing. Input of a small number of electrons to an Ag2 S island from a neighbored island causes Ag nanowire growth, which eventually connects the two islands. Shrinkage of an Ag nanowire also occurs depending on the distribution of a local electric potential. Thus, growth and shrinkage of Ag nanowires among Ag2 S islands shows dynamical change in conductive channels responding to input bias, which is demonstrated by an Ag2 S-island network surrounded by input/output electrodes. The Ag2 S islands that are electrically connected to a surrounding electrode are identified using a conductive-atomic force microscope, confirming the operating mechanism.